Wenn mehr gearbeitet würde – Potenziale des deutschen Arbeitsmarktes - Bernhard Boockmann; Gisela Meister-Scheufelen; Barbara Unger (Wirtschaftsdienst, 2025)
– The significant labour shortage in Germany could be alleviated if the domestic labour potential was better utilised. The most significant potential is found in part-time working women without children under the age of 14. If 50% of this group worked full time in the corresponding age groups, an additional 1.7 million full-time workers would be added to the labour market. Further potential lies in the targeted promotion of professional qualifications among mothers of children under the age of 14 and among older employees.
Keywords: J08; J21; 330; Arbeitsmarkt; Arbeitskräftepotenzial; Deutschland; Arbeitsmarkt; Arbeitskräftepotenzial; Deutschland